Monetary policy and real estate prices: A disaggregated analysis for Switzerland - Michael Berlemann; Julia Freese (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
Most empirical studies found that monetary policy has a significant effect on house prices while stock markets remain unaffected by interest rate shocks. In this paper we conduct a more detailed analysis by studying various sub-segments of the real estate market. Em-ploying a new dataset for Switzerland we estimate vector autoregressive models and find substitution effects between house and apartment prices on the one hand and rental prices on the other. Interestingly enough, commercial property prices do not react on interest rate variations.
Keywords: E43; E52; R21; 330; monetary policy; interest rate shocks; real estate; stock market